Ugly Betty - The Complete Second Series Episode 1-18 - Hayman, James; Brock, Tricia; Gates, Tucker; Berryman, Ross; Ferrera, America; Mabius, Eric; Williams, Vanessa
Major plotlines this season include the following: the love triangle between Betty, Henry, and a deli shop worker named Giovanni "Gio" Rossi; Claire's escape from prison, recapture, and trial for the murder of Fey Sommers; the aborted wedding of Wilhelmina Slater and Bradford Meade; Daniel and Alexis's power struggle after their father's death; Amanda's search for her biological father; Marc's relationship with fashion photographer Cliff St. Paul; Hilda's attempt to start her new beautician career and a relationship with Justin's gym teacher; Christina's reunion with her ailing husband; and Wilhelmina's scheme to conceive an heir to the Meade fortune using Bradford's sperm. [en.wikipedia.org]
Keywords: DVD-Video